The effect of a family-centered empowerment model on the hopefulness of parents with mentally retarded children - Saeideh Mazidi; Mohammad Ali Jahani; Seyed Amir Soltani; Golbahar Akhoundzadeh (حیات)
Background & Aim: Raising a mentally retarded child imposes significant psychological and economic burdens on families, which can adversely affect their sense of hope. The aim of the study was to determine the effect of a family-centered empowerment model on the hopefulness of parents with mentally retarded children. Methods & Materials: This clinical trial was conducted in 2023 in Aliabad Katol, focusing on parents with mentally retarded children. A total of 48 participants were selected through simple random sampling from a list of these parents and were randomly assigned to either an intervention group or a control group. Pre-test and post-test evaluations were conducted before and after the intervention. The intervention group participated in six family empowerment sessions, while the control group received routine care training. Data were collected using the Schneider's Hope Questionnaire. Statistical analysis was performed using SPSS version 23, employing univariate analysis of covariance, paired t-tests, and independent t-tests, with a significance level set at 0.05. Results: In the intervention group, the average age of mothers was 36.27±8.07 years, compared to 34.83±5.12 years in the control group. The average age of children was 11.88±2.88 years in the intervention group and 10.16±1.94 years in the control group. No significant difference was observed in the mean hope scores between the intervention and control groups prior to the intervention (P=0.582). However, post-intervention, the mean hope score significantly increased in the intervention group compared to the control group (P=0.021). After controlling for pre-test scores, a significant difference emerged between the groups (P<0.001, Eta=0.48), indicating that 48% of the variance in parents' hopefulness scores could be attributed to the effects of the family-centered empowerment model. Conclusion: Considering the effectiveness of the family-centered empowerment model in enhancing parents' hopefulness, as well as the crucial role that parents play in caring for mentally retarded children, this low-cost and effective intervention should be incorporated into programs aimed at supporting and empowering these parents. Clinical trial registry: IRCT20191229045934N1